An Improved MSA Model for Evaluating the Sound Transmission Loss of a Rectangular Plate for Diffuse Field Incidence - KIM, Myong-Jin; WON, Kyong-Su; RI, Chol-Su (Archives of Acoustics, 2019)
This paper presents an approximate analytical model for estimating the transmission loss (TL) of a finite rectangular plate in the low frequency range, which is based on the modal summation approach (MSA) taking into account the modal radiation impedance and fluid loading. The mode-dependent radiation resistance is calculated using the Rayleigh integral. The fluid loading is taken into account through the natural frequency modified by the added mass. The results are compared with the ones of Statistical Energy Analysis (SEA) coupled with FEM and FEM coupled with BEM. In addition, the effects of the various vibration modes and the fluid loading on TL, and a way for reducing the calculation time are discussed.